Prevalence and Risk Factors Associated with Hepatitis B and Hepatitis C Infections among Patients Undergoing Hemodialysis: A Single-Centre Study in Somalia - Mohamed Osman Omar Jeele; Rukia Omar Barei Addow; Faduma Nur Adan; Liban Hassan Jimale (International Journal of Nephrology)
Introduction. Hemodialysis patients have the highest risk for developing hepatitis B virus (HBV) and hepatitis C virus (HCV) than the general population. There is no study available for HBV and HCV in this population in Somalia. The main objective of this study is to determine the prevalence and risk factors of HBV and HCV infections among hemodialysis patients in Somalia. Methods. A cross-sectional assessment of hemodialysis patients from January 2021 to June 2021 was used in this study. 220 patients were included in this study. Age, sex, duration of hemodialysis, number of hemodialysis sessions per week, history of blood transfusion, HbsAg, and anti-HCV antibodies were examined. Results. Out of the 220 patients, males were predominant (113 (51.4%)). The mean age of the participants was 52.70. The prevalence of HBV was 7.3% (16 respondents), while the prevalence of HCV was 3.2% (7 respondents). 1 respondent (0.5%) had both HBV and HCV. There is a positive correlation between the duration of hemodialysis and the prevalence of HBV and HCV (r(218) = 0.298, p value <0.001), blood transfusion and prevalence of HBV and HCV (r(218) = 0.347, p value <0.001), and the number of hemodialysis sessions per week and prevalence of HBV and HCV (r(218) = 0.402, p value <0.001). The regression model of the combined predictors of history of blood transfusion, duration of hemodialysis, and number of dialysis sessions per week is R2 = 0.25, which indicates a 25% variance in the prevalence of HBV and HCV with a significance of F (3,216) = 23.67, p<0.001. Conclusions. The prevalence of HBV and HCV among hemodialysis patients in this study was 7.3% and 3.2%, respectively. 0.5% of the respondents had both HBV and HCV. History of blood transfusion, duration of hemodialysis, and number of hemodialysis sessions per week appear to have a strong correlation with the prevalence of HBV and HCV.